Chapter Per la conoscenza della terminologia delle arti fuori di Toscana fra Tre e Quattrocento. Con alcune spigolature da documenti bolognesi e ferraresi - ARESTI, ALESSANDRO (Proceedings e report, 2021)
The article is divided into three parts. In the first part, after referring to an ongoing project of an online re-release of artistic documents coming mainly from Tuscany (and Siena in particular) dating back to the XIVth and XVth centuries, and of creation of a glossary of the artistic and architectural terminology contained therein, the author announces his intention to expand the investigation to the extra-Tuscan terminologies in use in the centres or areas that played an important role in the domain of figurative arts in the period under consideration, to study the timeframe and means of their emergence and diffusion. For this purpose, the author believes that the archives of the Fabbricerie, related to the construction of large churches, could be fertile ground for documentary investigation. In the second part, the results of a first survey in the Archivio della Fabbrica di San Petronio, in Bologna, are followed by the examination of a few words extracted from two documents dating back to the end of the XIVth century. In the third part, the focus is on a rich anthology of artistic documents made available to experts by Adriano Franceschini, Artisti a Ferrara in età umanistica e rinascimentale, through which it is possible to know better the artistic vocabulary in Ferrara; also in this case, some lexical examples are provided.